2014
DOI: 10.1021/ci400541d
|View full text |Cite
|
Sign up to set email alerts
|

Dihedral-Based Segment Identification and Classification of Biopolymers I: Proteins

Abstract: A new structure classification scheme for biopolymers is introduced, which is solely based on main-chain dihedral angles. It is shown that by dividing a biopolymer into segments containing two central residues, a local classification can be performed. The method is referred to as DISICL, short for Dihedral-based Segment Identification and Classification. Compared to other popular secondary structure classification programs, DISICL is more detailed as it offers 18 distinct structural classes, which may be simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…3 In short, DISICL is based on the classification of segments of biopolymers. First, relevant (backbone) dihedral angles are calculated and attributed to regions in the dihedral angle space.…”
Section: Methodsmentioning
confidence: 99%
“…3 In short, DISICL is based on the classification of segments of biopolymers. First, relevant (backbone) dihedral angles are calculated and attributed to regions in the dihedral angle space.…”
Section: Methodsmentioning
confidence: 99%
“…70,71 More recently, it has been shown that secondary structure conformations can be classified solely on the basis of backbone dihedrals of a protein. 72,73 As a demonstration of our classification approach to realistic periodic data, we have applied our method to analyze the roughly to β sheets, α helices, turns, etc. (see Fig.…”
Section: Local Motifs Of a β-Hairpine Peptidementioning
confidence: 99%
“…The SS of all proteins was determined from the protein structure using three different algorithms: DSSP (Dictionary of Secondary Structure for Proteins) 28 , DISICL (DIhedral based Segment Identification and CLassification) 29 , and the in-house algorithm HbSS (Hydrogen-bond based Secondary Structure) described below. Table S4) based on their distinctive backbone hydrogenbonding patterns.…”
Section: Secondary Structure Determinationmentioning
confidence: 99%